2020
DOI: 10.4103/jfmpc.jfmpc_392_20
|View full text |Cite|
|
Sign up to set email alerts
|

Compliance to iron-folic-acid supplementation and associated factors among pregnant women: A cross-sectional survey in a district of West Bengal, India

Abstract: Background: Iron-deficiency anemia is considered to be a major health problem in India. This can complicate a normal pregnancy resulting in poor maternal and fetal outcomes. Iron-folic-acid (IFA) supplementation to antenatal and postnatal mothers given through the National Health Mission (NHM) serves as a major tool to combat this problem. Aim: This study aimed to assess compliance to IFA supplement and associated factors among antenatal mothers in a district of West Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The varying rates may be due to varying methods of measuring adherence. The proportion of participants who adhered to IFA in this study was comparable to a reported level of adherence of 81.8% by Debi et al, 42 among 208 pregnant women from India and a reported adherence of 82.2% by Maina-Gathigi et al, 43 among 381 pregnant women who accessed antenatal care from a teaching hospital in Kenya.…”
Section: Discussionsupporting
confidence: 85%
“…The varying rates may be due to varying methods of measuring adherence. The proportion of participants who adhered to IFA in this study was comparable to a reported level of adherence of 81.8% by Debi et al, 42 among 208 pregnant women from India and a reported adherence of 82.2% by Maina-Gathigi et al, 43 among 381 pregnant women who accessed antenatal care from a teaching hospital in Kenya.…”
Section: Discussionsupporting
confidence: 85%
“…Debi et al . [ 5 ] in rural areas of Hooghly district, West Bengal, have found the teenage pregnancy rate as 17.8%. Singh etal.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] have also found it to be overall 67.5% and Debi et al . [ 5 ] have found it to be >80%. The finding that the majority of the ever pregnant women from both the districts and communities in this study have either delivered or planned to deliver in a government health center signifies good utilization of the RCH services.…”
Section: Discussionmentioning
confidence: 99%
“…is said to be increased with age, birth order and single daily dose. 22 Another study from Nepal demonstrated that the role of influence of education status, ANC visits, delivery place and PNC visits influenced the compliance. 23 Another study from Ethiopia conducted on pregnant women at their ANC visits showed that IFA supplementation was 52.9%.…”
Section: Original Articlementioning
confidence: 99%
“…28 Studies concluded that the compliance of IFA is worse in lower socio-economic communities. 22 However, we could not explore the economic status of the current respondents to segregate their economic status.…”
Section: Original Articlementioning
confidence: 99%